Proteolyse in der Membran: Schutz für die Proteinhomöostase - Malchus, Nicole Susanne; Lemberg, Marius (Biospektrum, 2016)
Degradation of proteins is an important and essential mechanism to obtain the functionality and homeostasis of cells. A question that remained enigmatic for a long time was how membrane protein degra - dation is achieved and controlled. The discovery of intramembrane proteases shed new light on this question. These unusual enzymes are capable of hydrolyzing substrates within the hydrophobic membrane environment. It has been shown that intramembrane proteases play, on top of their signalling function, an important role in the degradation and abundance control of membrane proteins.
Gesehen am 06.05.2020